Incidence of Group B Streptococcus early onset sepsis in term neonates with second-line prophylaxis maternal intrapartum antibiotics: A multicenter retrospective study - Ming LOW, Jia (Elsevier BV, 2023)
10.1016/j.ajog.2023.10.035